Cathode component for discharge lamp and discharge lamp
By adopting a multi-layer structure design containing tungsten and high melting point metal in the cathode component for discharge lamps, the problems of insufficient heat dissipation and high cost are solved, and a longer life and a higher brightness maintenance rate are achieved.
Patent Information
- Application Number
- CN202080045366.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-06
- Filing Date
- 2020-08-06
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2040-08-06
AI Technical Summary
The existing cathode components for discharge lamps have insufficient heat dissipation properties under high temperature environments, resulting in insufficient life and an emitter material that does not contribute to the emission characteristics increases the cost.
The cathode component design is adopted for the first part containing tungsten and emitter material and the second part of the high melting point metal different from the emitter material. By adjusting the crystal particle size and structure of the tungsten and high melting point metal, the heat dissipation and durability are improved.
By improving the heat dissipation of the cathode component, its life is extended, the use of the emitter material is reduced, the cost is reduced, and the brightness maintenance rate of the discharge lamp is improved.
Smart Images

Figure CN114008742B_ABST
Abstract
Description
Technical Field
[0001] The embodiment relates to a cathode component for a discharge lamp and a discharge lamp. Background Art
[0002] Discharge lamps are roughly divided into two categories: low-pressure discharge lamps and high-pressure discharge lamps. Examples of low-pressure discharge lamps include various arc discharge type discharge lamps used in general lighting, special lighting used in roads or tunnels, paint curing devices, ultraviolet (UV) curing devices, sterilization devices, light cleaning devices for semiconductors, etc. Examples of high-pressure discharge lamps include water treatment devices, general lighting, outdoor lighting for arenas, etc., UV curing devices, exposure devices for semiconductors or printed circuit boards, etc., wafer inspection devices, high-pressure mercury lamps, metal halide lamps, ultra-high-pressure mercury lamps, xenon lamps, sodium lamps, etc. for projectors, etc. Discharge lamps like this are used in various devices such as lighting devices, image projection devices, and manufacturing devices.
[0003] An example of a cathode component for a discharge lamp (also referred to as a cathode component) controls the size of the tungsten crystal grain size in the side cross section and the circumferential cross section of the cathode component for a discharge lamp. As a durability test, a voltage is applied to the cathode component while it is energized and heated, and the emission current density (mA / mm 2 ) and the emission current density after 100 hours (mA / mm 2 ). The cathode component having the controlled crystal grain size exhibits excellent characteristics in the above durability test.
[0004] An example of the cathode component contains thorium oxide (ThO2) as an emitter material. An example of the cathode component includes a cylindrical shell portion and a tip portion with a pointed tip. An example of the cathode component is made of a tungsten alloy uniformly containing the emitter material. The emitter material at the front end of an example of the cathode component contributes to the emission characteristics, but sometimes the emitter material at the shell portion does not contribute to the emission characteristics.
[0005] The emitter material that does not contribute to the emission characteristics becomes a cause of increased costs. Another example of the cathode component includes a high-density sintered tungsten forged body and a porous tungsten layer. Another example of the cathode component can reduce the amount of emitter material used, achieve weight reduction, and save tungsten resources.
[0006] As for another example of the cathode component, although it can achieve light weight, the life of the cathode component for discharge lamp is sometimes insufficient. The use of the discharge lamp can cause the temperature of the front end of the cathode component to rise to about 2000°C. Therefore, by improving the heat dissipation of the cathode component, the life can be increased. When only the porous tungsten layer is provided, it may not be said that the improvement of heat dissipation is sufficient.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent No. 5800922
[0010] Patent Document 2: Japanese Patent Application Publication No. 2018-77945 Summary of the invention
[0011] The cathode component for a discharge lamp comprises a first part containing tungsten and an emitter material, and a second part containing a metal different from the emitter material. When the average crystal grain size of the tungsten phase in the first part is A μm and the average crystal grain size of the metal phase in the second part is B μm, A and B are numbers satisfying the formula: B>A. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is a schematic diagram showing a cross section in the longitudinal direction of an example of a cathode component for a discharge lamp having a tip integrated structure.
[0013] Figure 2 Yes means Figure 1 Schematic diagram of a cross section of the cathode component 1 in the wire diameter D direction shown in FIG.
[0014] Figure 3 This is an external view of the cathode component 1 having a fin structure.
[0015] Figure 4 It is a schematic diagram showing a cross section in the longitudinal direction of an example of a cathode component for a discharge lamp having a peripherally integrated structure.
[0016] Figure 5 It is a schematic diagram showing an example of the cathode member 1 having holes.
[0017] Figure 6 1 is a schematic diagram showing an example of the cathode member 1 including a support rod integrally formed with the high melting point metal portion 3 .
[0018] Figure 7 It is a diagram showing a structural example of a discharge lamp. DETAILED DESCRIPTION
[0019] The following is an explanation of the embodiments with reference to the accompanying drawings. The relationship between the thickness and the plane size of each component recorded in the drawings, the ratio of the thickness of each component, etc. are sometimes different from the actual object. In the embodiments, the same reference numerals are marked for substantially the same components, and the explanation is appropriately omitted.
[0020] Figure 1 It is a schematic diagram showing a cross section in the longitudinal direction of an example of a cathode component for a discharge lamp having a tip integrated structure. Figure 1The figure shows the cathode component 1, the tungsten part 2 (part 1), the high-melting-point metal part 3 (part 2), the center part 4-1 of the cathode component in the wire diameter direction, the bonding interface 5, the length T1 of the tungsten part 2, the length T2 of the high-melting-point metal part 3 and the wire diameter D of the high-melting-point metal part 3. Figure 2 Yes means Figure 1 Schematic diagram of a cross section of a cathode member 1 in a wire diameter D direction shown in FIG. The cathode member 1 includes a tungsten portion 2 and a high melting point metal portion 3 .
[0021] The cross section of the tungsten portion 2 in the longitudinal direction is as follows: Figure 1 As shown in , it has a tapered shape with a pointed tip. The taper angle is preferably 40 to 120 degrees.
[0022] The tungsten portion 2 contains tungsten (W) and an emitter material. The tungsten portion 2 is made of, for example, a tungsten alloy containing an emitter material. The emitter material is a material having a work function of 4.0 eV or less, and has an emission characteristic when a voltage is applied to the cathode member 1 .
[0023] The emitter material preferably includes at least one element selected from the group consisting of thorium (Th) and hafnium (Hf). Thorium can be included in the form of thorium oxide (ThO2), and the concentration of thorium can be calculated by converting ThO2. Hafnium can be included in the form of hafnium carbide (HfC), and the concentration of hafnium can be calculated by converting HfC.
[0024] The concentration of the emitter material of the tungsten portion 2 is preferably 0.1 mass% to 5 mass%, and further preferably 0.5 mass% to 3 mass%. If the concentration of the emitter material is less than 0.1 mass%, the emission characteristics are reduced. If the concentration of the emitter material exceeds 5 mass%, the emission characteristics are saturated, which also becomes a factor of cost increase. The concentration of thorium is more preferably 0.5 mass% to 3 mass%. Thorium and hafnium have high emission characteristics, so performance can be obtained at the above concentrations.
[0025] The high melting point metal portion 3 is, for example, Figure 1 As shown in , it is arranged on the lower side of the tungsten part 2. The high melting point metal part 3 contains a metal different from the emitter material. The high melting point metal part 3 contains, for example, a high melting point metal as a main component. The so-called main component is the element that contains the most of the constituent elements, and the element of the main component contains, for example, more than 50 atomic % of the whole. The high melting point metal part 3 may not contain the emitter material, or may contain the emitter material.
[0026] The melting point of the high melting point metal is, for example, not less than 2300° C. The temperature of the cathode component for a discharge lamp may rise to approximately 2000° C. during use. Therefore, it is preferable to use a high melting point metal.
[0027] Examples of high melting point metals include tungsten and molybdenum (Mo). The melting point of tungsten is 3422°C, and the melting point of molybdenum is 2623°C. Since tungsten and molybdenum have high melting points, they are durable even at the operating temperature of the cathode component for discharge lamps. Therefore, the metal contained in the high melting point metal portion 3 preferably contains at least one metal element selected from the group consisting of tungsten and molybdenum.
[0028] The high melting point metal portion 3 may include, for example, at least one selected from the group consisting of a doped tungsten alloy, a tungsten alloy containing lanthanum oxide, a tungsten-molybdenum alloy, pure tungsten, and pure molybdenum. These materials all have a high melting point of 2300° C. or more.
[0029] The doped tungsten alloy contains, for example, at least one doping material selected from the group consisting of potassium (K), silicon (Si), and aluminum (Al). The concentration of the doping material is, for example, 500 mass ppm or less. The doping material does not correspond to the emitter material.
[0030] The tungsten alloy containing lanthanum oxide is a tungsten alloy containing 1 mass % to 2 mass % of lanthanum oxide in terms of La2O3. The tungsten-molybdenum alloy contains 1 mass % to 50 mass % of molybdenum.
[0031] Pure tungsten contains 99.9 mass % or more of tungsten. Pure molybdenum contains 99.9 mass % or more of molybdenum.
[0032] Figure 3 This is an appearance diagram of a cathode component for a discharge lamp having a fin structure. Figure 3 The figure shows the cathode component 1, the tungsten part 2, the high melting point metal part 3 and the fin structure 6. For other descriptions of the tungsten part 2 and the high melting point metal part 3, please refer to the Figure 1 Detailed description of the tungsten portion 2 and the high melting point metal portion 3 shown in FIG.
[0033] The fin structure 6 is preferably provided on a part or the whole of the outer peripheral surface of the high melting point metal part 3. The fin structure 6 has fins. The fin structure 6 is formed by providing at least one selected from the group consisting of convex parts and concave parts on the outer peripheral surface of the high melting point metal part 3, and the surface area can be increased. Since the discharge lamp is kept in a vacuum, the radiation effect can be obtained by increasing the surface area. The shape of the fin structure 6 can be listed as various shapes such as thread groove, V-shaped cross section, U-shaped cross section, S-shaped surface, protrusion type, rough surface, low density, straight line, wave shape, etc.
[0034] The diameter of the fin of the fin structure 6 is the maximum diameter of the part in contact with the high melting point metal part 3. The height of the fin is the maximum height from the root of the fin (the contact part with the high melting point metal part 3). The vertex spacing of adjacent fins is the spacing (spacing) between the vertices of the nearest fins. The vertex spacing of adjacent fins is preferably greater than 1 mm. When multiple fins are provided, the diameter, height, and spacing may all be the same or may be different. As long as the above preferred range is met, the cooling efficiency can be improved. Adjacent fins may have gaps between each other or may be a continuous shape.
[0035] The height of the fin is preferably 10 μm or more. When the fin is a convex portion, the height of the convex portion relative to the surface of the high-melting-point metal portion 3 is the height of the fin. When the fin is a concave portion, the depth of the concave portion relative to the surface of the high-melting-point metal portion 3 is the height of the fin. When the height of the fin is less than 10 μm, the effect of increasing the surface area may become insufficient. The upper limit of the height of the fin is not particularly limited, but is preferably less than 5 mm. If it exceeds 5 mm, the strength of the high-melting-point metal portion 3 is sometimes reduced, or the size becomes uselessly large. Therefore, the height of the fin is preferably 10 μm to 5 mm, 0.1 mm to 3 mm, or 0.3 mm to 3 mm.
[0036] The diameter or minimum width of the fin is preferably 1 mm or more. The so-called diameter of the fin is the maximum diameter when the convex fin is observed from above. For example, in the case where a conical fin is provided at the high-melting-point metal portion 3, the root of the cone becomes the maximum diameter. The minimum width of the fin is the minimum width of the concave fin. For example, in the case where a groove is provided along the outer periphery of the high-melting-point metal portion 3, the width of the groove becomes the minimum width.
[0037] The vertex interval (pitch) between adjacent fins is preferably 1 mm or more. It is preferred that a plurality of fins be provided. By providing a plurality of fins, the surface area can be further increased. If the pitch of the fins is less than 1 mm, the strength of the gap between the fins may be reduced.
[0038] The width of the fin shape is preferably in the range of 0.5 mm to 3 mm. In the case of a groove, the minimum width is the width of the fin shape. In the case of a protrusion, it is the maximum diameter when the protrusion is viewed from above. When multiple fins are provided, the pitch is preferably in the range of 1 mm to 5 mm.
[0039] Figure 4 It is a schematic diagram showing a cross section in the longitudinal direction of an example of a cathode component for a discharge lamp having a peripherally integrated structure. Figure 4 The figure shows the cathode member 1 , the tungsten portion 2 , the high melting point metal portion 3 , the longitudinal center portion 4 - 2 of the cathode member 1 , the bonding interface 5 , the wire diameter D1 of the high melting point metal portion 3 , and the wire diameter D2 of the tungsten portion 2 .
[0040] The cathode component 1 includes a tungsten portion 2 and a high melting point metal portion 3. The high melting point metal portion 3 is provided so as to surround the tungsten portion 2 in the cross section of the cathode component 1 in the wire diameter direction. For other descriptions of the tungsten portion 2 and the high melting point metal portion 3, reference may be made as appropriate. Figure 1 Detailed description of the tungsten portion 2 and the high melting point metal portion 3 shown in FIG.
[0041] The cross section of the tungsten portion 2 in the longitudinal direction is as follows: Figure 4 As shown in FIG. , it has a conical shape with a pointed front end. Figure 4 In FIG. 5 , the high melting point metal portion 3 also has a tapered shape that matches the tapered shape of the tungsten portion 2 , but only the tungsten portion 2 may be provided with a tapered shape. Figure 3 The lower surface of the middle tungsten portion 2 and the lower surface of the high melting point metal portion 3 are at the same level, but one may be lower than the other. In particular, the end surface of the tungsten portion 2 may be lowered to form a hole for mounting the electrode support rod.
[0042] When the average crystal grain size of the tungsten phase of the tungsten portion 2 is A μm and the average crystal grain size of the metal phase of the high melting point metal portion 3 is B μm, A and B are numbers that satisfy the formula: B>A. In other words, the average crystal grain size of the metal phase of the high melting point metal portion 3 is larger than the average crystal grain size of the tungsten phase of the tungsten portion 2.
[0043] The discharge lamp using the cathode member 1 is kept in a vacuum. The temperature of the tungsten portion 2 may rise to about 2000° C. Therefore, it is preferable to conduct the heat from the tungsten portion 2 to the high melting point metal portion 3 and dissipate it.
[0044] Polycrystalline materials have grain boundaries between crystals. Grain boundaries are an obstacle to heat conduction. In contrast, by increasing the average crystal grain size of the metal phase of the high-melting-point metal portion 3, the number of grain boundaries can be reduced. As a result, the heat generated by the tungsten portion 2 can be easily dissipated from the high-melting-point metal portion 3. As a result, the temperature rise of the electrode of the cathode component can be suppressed, and the life of the discharge lamp can be increased.
[0045] A and B are preferably numbers satisfying the formula: B ≥ 1.5A. In other words, the average crystal grain size of the metal phase of the high melting point metal portion 3 is preferably 1.5 times or more the average crystal grain size of the tungsten phase of the tungsten portion 2. This can improve the heat dissipation effect.
[0046] The average crystal grain size of the tungsten phase of the tungsten portion 2 is preferably 5 μm to 15 μm. The emitter material is dispersed in the crystal grain boundaries of the tungsten phase. If the above average crystal grain size is less than 5 μm or exceeds 15 μm, it may be difficult to uniformly disperse the emitter material. Therefore, the above average crystal grain size is preferably 5 μm to 15 μm, and further 7 μm to 12 μm.
[0047] The average crystal grain size of the metal phase of the high-melting-point metal part 3 is preferably 18 μm to 40 μm. When the average crystal grain size is less than 18 μm, the heat dissipation effect is small. If the average crystal grain size exceeds 40 μm, the heat dissipation effect is improved, but the strength of the high-melting-point metal part 3 may be reduced. In addition, in the case of installing an electrode support rod at the high-melting-point metal part 3 to manufacture a cathode component, if the strength of the high-melting-point metal part 3 is reduced, it may sometimes cause breakage when the electrode support rod is installed. Similarly, it is possible to be broken during processing when setting the fin structure. Therefore, the average crystal grain size is preferably 18 μm to 40 μm, and further 20 μm to 36 μm.
[0048] When an electron beam backscatter diffraction (EBSD) analysis is performed on a region located within 1 mm from the center portion 4-1 or the center portion 4-2 in a cross section passing through the center portion 4-1 or the center portion 4-2 and along the length direction of the tungsten portion 2 and having a unit area of 90 μm×90 μm, in an inverse pole figure (IPF) image in the length direction, there is a <111> The area ratio of the tungsten phase in a crystal orientation having an orientation difference of -15 to 15 degrees is preferably 15% to 50%.
[0049] Furthermore, when performing electron beam backscatter diffraction analysis of a region located within 1 mm from the center 4-1 or the center 4-2 of the high-melting-point metal portion 3 and along the length direction of the high-melting-point metal portion 3 and having a unit area of 90 μm×90 μm, in an Inverse Pole Figure image in a direction perpendicular to the cross section, it is preferred that the region with respect to <111> The area ratio of the metal phase having a crystal orientation with an orientation difference of -15 to 15 degrees is lower than the area ratio of the tungsten phase. Thus, the heat of the high melting point metal part 3 can be easily conducted to the electrode support rod.
[0050] The center portion 4-1 of the high melting point metal portion 3 is the center portion of the cathode component 1 of the front end integral structure. The center portion 4-2 of the high melting point metal portion 3 is the center portion of the cathode component 1 of the surrounding integral structure. The center portion 4-1 and the center portion 4-2 are collectively referred to as the center portion 4.
[0051] The average crystal grain size of the tungsten phase and the average crystal grain size of the above-mentioned metal phases were determined from the grain image obtained by EBSD. The measurement locations are as follows.
[0052] In the case of the front end integrated structure, prepare a cross section in the longitudinal direction of the cathode component 1 and a cross section passing through the center portion 4-1. Set the portion within 1 mm from the center portion 4-1 of the cross section as the measurement portion. Select the measurement portion from the tungsten portion 2 and the high melting point metal portion 3 respectively. The measurement surface of the measurement sample is polished until the surface roughness Ra becomes less than 0.8 μm.
[0053] In the case of the peripheral integrated structure, the measurement position of the tungsten part 2 is selected by the same method as the case of the front end integrated structure. In the case of the peripheral integrated structure, a cross section in the longitudinal direction of the cathode member 1 and a cross section passing through the center part 4-2 are prepared. A position within 1 mm from the position passing through the center part 4-2 in the high melting point metal part 3 is set as the measurement position.
[0054] The EBSD grain image is a diagram that identifies the same grain when there are two or more consecutive measurement points with a crystal orientation angle difference of less than 5 degrees in a unit area of 90 μm×90 μm. The average crystal grain size is calculated from the area of the identified grains in a unit area of 90 μm×90 μm. The grain size becomes the equivalent circle diameter.
[0055] For particles overflowing from a unit area of 90 μm×90 μm, the boundary of the unit area of 90 μm×90 μm was calculated as the crystal grain boundary. The average crystal grain size obtained was the median grain size (average grain size D 50 ). That is, it becomes the cumulative particle size.
[0056] EBSD is the process of irradiating a crystalline sample with electron beams. Electrons are diffracted and emitted from the sample as reflected electrons. The diffraction pattern is projected, and the crystal orientation can be determined from the projected pattern. X-ray diffraction (XRD) is a method of determining the average value of the crystal orientation of multiple crystals. In contrast, EBSD can determine the crystal orientation of each crystal. The same analysis method as EBSD is sometimes called electron beam backscatter pattern (EBSP) analysis.
[0057] The EBSD analysis was performed using a thermal field emission scanning electron microscope (TFE-SEM) JSM-6500F manufactured by JEOL Ltd., a Digi View IV slow scan CCD camera manufactured by TSL Solutions Ltd., OIM Data Collection ver. 7.3x, and OIM Analysis ver. 8.0.
[0058] The measurement conditions of EBSD analysis include: electron beam acceleration voltage 20kV, irradiation current 12nA, sample tilt angle 70 degrees, unit area of measurement area 90μm×90μm, measurement position within 1mm from the center 4, and measurement interval 0.3μm / step. The above cross section is the measurement surface, and the above cross section is irradiated with electron beams to obtain a diffraction pattern. The measurement surface of the measurement sample is polished until the surface roughness Ra becomes less than 0.8μm.
[0059] Crystal orientation uses basic vectors to indicate directions. A combination of square brackets ([]) and numbers enclosed in the square brackets indicates only a specific crystal orientation. A combination of angle brackets (<>) and numbers enclosed in the angle brackets indicates a specific crystal orientation and its equivalent direction. For example, <111> The orientation representation includes directions equivalent to
[111] .
[0060] The so-called IPF image is a crystal orientation map. The IPF image can be used to find the ratio of the area that deviates from the specified crystal orientation. The IPF image can be obtained based on the above-mentioned EBSD measurement method. Through the color image, the area ratio can be easily obtained by image analysis.
[0061] The cross section through the center portion 4 of the tungsten portion 2 <111> It represents the orientation in the vertical direction with respect to the cross section passing through the center portion 4. <111> The orientation of the cathode component 1 makes it easier for heat to escape to the outside. Thus, the heat dissipation of the cathode component 1 can be improved.
[0062] The cross section passing through the center portion 4-1 or the center portion 4-2 of the high melting point metal portion 3 is <111> It indicates the orientation in the direction perpendicular to the cross section passing through the center portion 4 .
[0063] The high melting point metal portion 3 has a relative <111> The area ratio of the metal phase having a crystal orientation with an orientation difference of -15 to 15 degrees is preferably 5% to 90%. <111> Different orientations have the effect of suppressing the grain growth of the high melting point metal portion 3. <111> orientation, heat becomes easy to dissipate outwards.
[0064] The tungsten portion 2 and the high melting point metal portion 3 have relative <111> The area ratio of the phase with a crystal orientation having an orientation difference of -15 to 15 degrees is preferably 5% to 40%. <111> Even after the heat treatment, the relationship satisfying the formula: B>A can be maintained. The cathode component 1 is sometimes subjected to heat treatment when mounted in a discharge lamp. Examples of the heat treatment include recrystallization heat treatment and stress relief heat treatment. <111> The cross section shows a vertical orientation. By having a vertical orientation, abnormal grain growth accompanying heat treatment can be suppressed. Therefore, the cathode component 1 of the embodiment can satisfy the formula: B>A even after heat treatment.
[0065] Even if the cathode member 1 is a peripheral integrated structure, A and B satisfy the formula: B>A. By increasing B, the heat dissipation effect can be improved. More preferably, A and B satisfy the formula: B≥1.5A.
[0066] It is preferable that the bonding interface 5 has irregularities at least in a portion thereof. The irregularities in the bonding interface can generate an anchor effect between the tungsten portion 2 and the high melting point metal portion 3 and improve the bonding strength.
[0067] The value of the concavoconvex is defined by the difference between the deepest part of the concave part and the top of the convex part. The value of the concavoconvex is preferably above 0.01mm, and further above 0.1mm. By making the concavoconvex of 0.01mm or more, the bonding strength can be set to above 200MPa. If the bonding strength is improved, the breakage of the electrode support rod during pressing, the breakage during handling, etc. can be suppressed. The upper limit of the concavoconvex is not particularly limited, but preferably below 1mm. If it exceeds 1mm, it is possible that the concavoconvex is too large and a gap is generated in the bonding interface. Therefore, the concavoconvex of the bonding interface is preferably 0.01mm to 1mm, and further 0.1mm to 0.5mm. If it is within this range, the bonding strength can be set to above 200MPa, and further above 400MPa.
[0068] The bonding strength is measured by a peel test. The bonding strength is measured by a 4-point bending test. The test piece is set so that the bonding interface enters between the internal fulcrum and the external fulcrum, and the load is applied. The bonding strength is calculated from the maximum load when the test piece breaks. The 4-point bending test is carried out in accordance with JIS R1631 (room temperature bending strength test method for fine ceramics).
[0069] The concavity and convexity of the bonding interface 5 can be confirmed by laser microscope observation of the cross section. If there are concavities and convexities at the bonding interface 5, the concavities and convexities will be generated in the distribution state of the emitter material. In the laser microscope photo, the emitter material appears black. Since the contrast is different from tungsten or high melting point metal, it can be identified.
[0070] The laser microscope photograph can be obtained by observing the sample at a magnification of 500 to 1500 times and a measurement field of 200 μm×200 μm or more. If the emitter material region in the laser microscope photograph is connected with a line, the concavo-convex shape can be confirmed.
[0071] The concavoconvexity of the bonding interface 5 can also be confirmed by cross-sectional scanning electron microscope (SEM) observation and energy dispersive X-ray analysis (EDS). Tungsten or high melting point metal and emitter material can be identified by elemental analysis. If there are concavoconvexities at the bonding interface 5, concavoconvexities will be generated in the distribution state of the emitter material. In the SEM observation, the sample is observed at 500 times to 1500 times and the measurement field is 200μm×200μm or more. If the emitter material area identified by elemental analysis is connected with a line, the concavoconvex shape can be confirmed.
[0072] The wire diameter D of the cathode component 1 is preferably 2 mm to 35 mm. In the case of the front integrated structure, the diameter of the high melting point metal part 3 is the wire diameter D. In the case of the peripheral integrated structure, the wire diameter D1 of the high melting point metal part 3 is the wire diameter D. If the wire diameter D is less than 2 mm, there is a possibility that the emission characteristics may be insufficient. If the wire diameter D exceeds 35 mm, the above effects may not be obtained.
[0073] In the case of a front-end integrated structure, the length T1 of the tungsten portion 2 and the length T2 of the high-melting-point metal portion 3 are preferably within the range of 0.4≤T2 / T1≤3. In the case of a peripheral integrated structure, the wire diameter D1 of the high-melting-point metal portion 3 and the wire diameter D2 of the tungsten portion 2 are preferably within the range of 0.2≤D2 / D1≤0.8. By adjusting the ratio T2 / T1 or the ratio D2 / D1, the reduction in emission characteristics can be suppressed even if an emitter material is not added to the high-melting-point metal portion 3. That is, the use of an emitter material that does not contribute to the emission characteristics can be prevented. By suppressing the amount of emitter material used, manufacturing costs can be reduced.
[0074] Figure 5 Schematic diagram showing an example of a cathode component 1 having a hole. The high melting point metal portion 3 may also be Figure 5 As shown in FIG. 1 , the refractory metal portion 3 has a hole 7. The hole 7 is a hole for joining the electrode support rod. The hole 7 is provided on the lower surface of the high melting point metal portion 3 (the side where the tungsten portion 2 is not provided).
[0075] The support rod 8 may be joined by various methods such as press fitting and brazing. A thread groove may be provided inside the hole 7. A thread groove may be provided on the support rod 8 to form a spiral. As long as the thread groove is provided, the high melting point metal portion 3 can be prevented from being damaged when the support rod 8 is installed.
[0076] Figure 61 is a schematic diagram showing an example of a cathode component 1 having a support rod integrally formed with the high melting point metal portion 3. By integrating the support rod 8 with the high melting point metal portion 3, the process of providing a hole and the process of joining the support rod 8 are no longer necessary. Therefore, the manufacturing cost can be reduced. It should be noted that the length of the support rod 8 is not limited to Figure 5 and Figure 6 Length shown in .
[0077] The three-point bending strength of the high melting point metal part 3 is preferably 100 MPa to 600 MPa. For example, by using a sintered body formed by forging or rolling to manufacture the cathode component, a three-point bending strength of 700 MPa or more can be achieved. This is because a dense sintered body with few voids can be formed.
[0078] The cathode component for a discharge lamp is exposed to a high temperature environment during the lighting of the discharge lamp. Therefore, durability under high temperature is required. On the other hand, the physical strength requirement is small. In order to achieve a three-point bending strength of 100MPa to 600MPa, it is effective to reduce the density of the cathode component. For example, the density can be changed by using a modeling technology (3D printing) using a 3D printer.
[0079] For strength control, forming pores is effective. The proportion of pores is preferably within the range of 0% to 60% per unit area of 200 μm×200 μm or more in terms of area ratio. If the proportion of pores exceeds 60% in terms of area ratio, the three-point bending strength may be reduced to less than 100 MPa.
[0080] The area ratio of the pores can be measured by observing any cross section of the high melting point metal portion 3 with an optical microscope such as a laser microscope. The magnification is set to 100 times or more. In the optical microscope photograph, the pores are seen as black contrast. High melting point metals such as tungsten appear gray. Calculate the area ratio of black that is 200μm×200μm or more per unit area. Perform this operation at any three locations, and set the average value as the area ratio of the pores.
[0081] When the high melting point metal portion 3 does not contain an emitter material, the oxygen concentration is preferably 0.1 mass % or less. The emitter material is sometimes added in the form of an oxide such as thorium oxide. On the other hand, oxygen that is not a constituent element of the emitter material becomes impurity oxygen. If the concentration of oxygen exceeds 0.1 mass %, the strength is sometimes reduced. Therefore, the oxygen concentration of the high melting point metal portion 3 is preferably 0.1 mass % or less, and further 0.05 mass % or less. The oxygen concentration of the high melting point metal portion 3 is measured, for example, by semi-quantitative analysis of SEM-EDX, or by crushing the high melting point metal portion 3 and then measuring it by infrared absorption method.
[0082] The cathode component of the embodiment can be applied to a discharge lamp. Figure 7It is a diagram showing a structural example of a discharge lamp. Figure 7 The discharge lamp 20 shown in FIG. 1 includes a cathode member 1 , a support rod 8 as a cathode electrode support rod, an anode member 9 , a support rod 10 as an anode electrode support rod, and a glass tube 11 .
[0083] The cathode component 1 is connected to the support rod 8. The anode component 9 is connected to the support rod 10. The connection is performed by pressing, brazing, etc. The cathode component 1 and the anode component 9 are arranged opposite to each other in the glass tube 11, and are sealed together with a part of the support rod 8 and a part of the support rod 10. The inside of the glass tube 11 is kept in vacuum.
[0084] The cathode component 1 can be applied to any discharge lamp of a low-pressure discharge lamp or a high-pressure discharge lamp. Examples of low-pressure discharge lamps include various arc discharge type discharge lamps used in general lighting, special lighting used in roads or tunnels, paint curing devices, UV curing devices, sterilizing devices, semiconductor and other light cleaning devices, etc. Examples of high-pressure discharge lamps include water treatment devices, general lighting, outdoor lighting such as arenas, UV curing devices, exposure devices for semiconductors or printed circuit boards, wafer inspection devices, high-pressure mercury lamps, metal halide lamps, ultra-high-pressure mercury lamps, xenon lamps, sodium lamps, etc. for projectors, etc. Discharge lamps like this are used in various devices such as lighting devices, image projection devices, and manufacturing devices.
[0085] The cathode component of the embodiment has improved heat dissipation, so that temperature rise can be suppressed. The durability of the cathode component 1 can be improved, so that the brightness maintenance rate of the discharge lamp can be suppressed from decreasing. Therefore, it is particularly suitable for high-pressure discharge lamps.
[0086] Next, an example of a method for manufacturing the cathode component of the embodiment will be described. The method for manufacturing the cathode component of the embodiment is not particularly limited as long as it has the above-mentioned configuration, and the following method can be cited as a method for manufacturing the cathode component with a high yield.
[0087] First, a method for manufacturing the tungsten portion 2 will be described. The tungsten portion 2 includes a tungsten alloy containing an emitter material. Here, a method for manufacturing the tungsten portion 2 using thorium as the emitter material will be described.
[0088] Preparation of thorium-containing tungsten alloy powder. Examples of the method for preparing the tungsten alloy powder include a wet method and a dry method.
[0089] In the wet method, first, a process of preparing tungsten material powder is implemented. The tungsten material powder can include ammonium tungstate (APT) powder, metal tungsten powder, and tungsten oxide powder. The tungsten material powder can be one of them, or two or more of them can be used. Ammonium tungstate powder is preferred because it is relatively cheap. The average particle size of the tungsten material powder is preferably less than 5 μm.
[0090] When using ammonium tungstate powder, the ammonium tungstate powder is heated at a temperature of 400°C to 600°C in the air or in an inert atmosphere (nitrogen, argon, etc.) to change the ammonium tungstate powder into tungsten oxide powder. At a temperature below 400°C, the ammonium tungstate powder is not fully changed into tungsten oxide powder. At a temperature exceeding 600°C, the particles of the tungsten oxide powder become coarse, and uniform dispersion with thorium oxide powder in the subsequent process becomes difficult. Through this process, tungsten oxide powder is prepared.
[0091] Next, a process of adding thorium material powder and tungsten oxide powder to the solution is implemented. Examples of thorium material powder include metallic thorium powder, thorium oxide powder, and thorium nitrate powder. Among them, thorium nitrate powder is preferred. Thorium nitrate powder is easy to mix evenly in a liquid. Through this process, a solution containing thorium material powder and tungsten oxide powder is prepared. It is preferred to add thorium material powder in a manner that is the same as the final concentration of thorium oxide or a slightly higher concentration. The average particle size of the thorium material powder is preferably less than 5 μm. The solution is preferably pure water.
[0092] Next, a step of evaporating the liquid component of the solution containing the thorium material powder and the tungsten oxide powder is performed. Next, a decomposition step of heating the thorium material powder such as thorium nitrate at a temperature of 400°C to 900°C in an air atmosphere to change it into a thorium oxide powder is performed. Through this step, a mixed powder containing thorium oxide powder and tungsten oxide powder can be prepared. The thorium oxide concentration of the obtained mixed powder containing thorium oxide powder and tungsten oxide powder is measured. When the concentration is low, it is preferred to add tungsten oxide powder.
[0093] Next, a step of reducing the tungsten oxide powder to metallic tungsten powder is performed by heating the mixed powder containing the thorium oxide powder and the tungsten oxide powder in a reducing atmosphere such as hydrogen at a temperature of 750° C. to 950° C. This step can prepare tungsten powder containing thorium oxide powder.
[0094] A method of mixing metal tungsten powder with thorium material powder is also effective. The metal tungsten powder is preferably formed by forming tungsten oxide powder from ammonium tungstate powder and reducing the obtained tungsten oxide. When the ammonium tungstate powder is changed into tungsten oxide powder, the obtained tungsten oxide preferably has oxygen deficiency. The composition of tungsten oxide is stable as WO3. If there is oxygen deficiency, it becomes WO 3-x , x>0. If there is oxygen deficiency, deformation is formed in the crystal structure. The metal tungsten powder obtained by reduction in this state has a high effect of suppressing abnormal grain growth. The value of x is preferably in the range of 0.05≤x≤0.30.
[0095] The process of forming tungsten oxide powder from ammonium tungstate powder is preferably a process of heating in an inert atmosphere. The so-called inert atmosphere is a nitrogen atmosphere or an argon atmosphere. In order to control the value of x, it is possible to cite methods such as reducing the amount of oxygen in the inert atmosphere (for example, less than 1 volume %) and mixing hydrogen. The heat treatment temperature is preferably in the range of 400°C to 600°C. When it is lower than 400°C, the reaction rate is slow and mass productivity is reduced. If it exceeds 600°C, there is a possibility of excessive grain growth.
[0096] Will WO 3-x The powder reduction step is preferably performed in a hydrogen-containing atmosphere. The heat treatment temperature is preferably in the range of 600°C to 800°C. When the heat treatment temperature is lower than 600°C, the reduction rate is slow and mass productivity is reduced. If it exceeds 800°C, excessive grain growth may occur.
[0097] Next, a step of evaporating the liquid component of the solution containing the thorium material powder and the metal tungsten powder is performed. Next, a decomposition step of heating the sample at a temperature of 400°C to 900°C in an air atmosphere to convert the thorium material powder such as thorium nitrate into thorium oxide powder is performed. Through this step, tungsten powder containing thorium oxide powder can be prepared.
[0098] The dry method first prepares thorium oxide powder. Then, the thorium oxide powder is crushed and mixed using a ball mill. This process can break up the agglomerated thorium oxide powder and reduce the agglomerated thorium oxide powder. During the mixing process, a small amount of metal tungsten powder can also be added.
[0099] The thorium oxide powder after the pulverization and mixing is preferably sieved as necessary to remove incompletely pulverized agglomerated powder or coarse particles. It is preferred to remove agglomerated powder or coarse particles having a maximum diameter exceeding 10 μm by sieving.
[0100] Next, a step of mixing the metal tungsten powder is performed. The metal tungsten powder is added in such a way that the thorium oxide concentration as the final purpose is achieved. The mixed powder of the thorium oxide powder and the metal tungsten powder is placed in a mixing container, and the mixing container is rotated and uniformly mixed. At this time, the mixing container in a cylindrical shape is rotated in a circumferential direction, so that the mixing can be smoothly performed. Through this process, tungsten powder containing thorium oxide powder can be prepared.
[0101] When hafnium is used as the emitter material, the dry method is suitable. The emitter material is mixed so as to have a content of 0.1 mass % to 5 mass %.
[0102] Next, the obtained tungsten powder containing the emitter material is used to prepare a molded body. When forming the molded body, a binder may be used as needed. The molded body is preferably cylindrical. The length of the molded body is arbitrary.
[0103] Next, a step of pre-sintering the molded body is performed. The pre-sintering is preferably performed at a temperature of 1250° C. to 1500° C. Through this step, a pre-sintered body can be obtained.
[0104] Next, a process of conducting electric sintering on the pre-sintered body is implemented. It is preferred that the electric sintering is conducted in such a way that the temperature of the sintered body becomes 2100°C to 2500°C. When the temperature is lower than 2100°C, sufficient densification cannot be performed, and sometimes the strength is reduced. If it exceeds 2500°C, sometimes the thorium oxide particles and tungsten particles grow excessively and the desired crystalline structure cannot be obtained. Through this process, a tungsten alloy sintered body containing thorium oxide can be obtained. As long as the pre-sintered body has a cylindrical shape, the sintered body also has a cylindrical shape.
[0105] Next, the first processing step is performed to adjust the wire diameter of the cylindrical sintered body (ingot) by forging, rolling, extrusion, etc. The processing rate of the first processing step is preferably within a range of 10% to 30%.
[0106] The second working step is performed after the first working step. The second working step is preferably a rolling process with a working rate of 30% to 70%, and more preferably a rolling process with a working rate of 40% to 70%.
[0107] The processing rate is calculated by processing rate = [(CD) / C] × 100%, when the cross-sectional area of the cylindrical sintered body before processing is set as C and the cross-sectional area of the cylindrical sintered body after processing is set as D. For example, the processing rate of processing a cylindrical sintered body with a diameter of 25 mm into a cylindrical sintered body with a diameter of 20 mm is described. Since the cross-sectional area C of a circle with a diameter of 25 mm is 460.6 mm 2 , the cross-sectional area D of a circle with a diameter of 20 mm is 314 mm 2 , so the processing rate becomes 32% = [(460.6-314) / 460.6]×100%.
[0108] The processing rate of the first processing step is 10% to 30% and is obtained by setting the cross-sectional area of the cylindrical sintered body (ingot) before the first processing step as the cross-sectional area C. The processing rate of the second processing step is 30% to 70% and is obtained by setting the cross-sectional area of the cylindrical sintered body after the first processing step as the cross-sectional area C.
[0109] Forging is a process in which a sintered body is struck with a hammer to apply pressure. Rolling is a method in which a sintered body is processed while being clamped between two or more rolls. Extrusion is a method in which a sintered body is extruded from a die hole by applying strong pressure.
[0110] The first processing step preferably includes at least one processing selected from the group consisting of forging, rolling and extrusion. These processing methods can reduce the wire diameter. Therefore, the pores in the cylindrical sintered body can be reduced. The first processing step is preferably forging or extrusion. Forging or extrusion is easy to process the entire circumference of the cylindrical sintered body, so the effect of reducing pores is high.
[0111] The processing rate of the first processing step is preferably 10% to 30%. If the processing rate is less than 10%, the effect of reducing pores is small. If the processing rate exceeds 30%, it becomes difficult to control the crystal orientation. As long as the processing rate of the first processing step is within the range of 10% to 30%, it can also be divided into multiple times for processing.
[0112] The second processing step is rolling. If rolling is used, it is easy to control the crystal orientation. Rolling is a method of reducing the cross-sectional area while clamping with multiple rollers. If only rolling is used for processing, the crystal orientation can be controlled.
[0113] In forging, the crystal orientation is easily uneven because it is struck with a hammer. In extrusion, the stress when passing through the die is strong, so the crystal orientation is easily different between the center and the surface. In rolling, the stress from the roller can be adjusted, so the crystal orientation is easy to control.
[0114] The processing rate of the rolling process in the second processing step is 30% to 70%. The cross-sectional area after the first processing step is set as the cross-sectional area C to control the processing rate. As long as the processing rate is within the range of 30% to 70%, it can be processed once or divided into 2 or more times. If the processing rate is less than 30% or exceeds 70%, the target crystal orientation cannot be obtained.
[0115] The first processing step and the second processing step are preferably cold working. Cold working is a method of processing an object at a temperature below the recrystallization temperature. Processing in a heated state above the recrystallization temperature is called hot working. If hot working, the cylindrical sintered body recrystallizes. If cold working, it will not recrystallize. It is important to control the crystal orientation with a structure that will not recrystallize.
[0116] By setting the cold working, it is possible to suppress the increase in the average crystal grain size of the tungsten phase of the tungsten portion 2. By controlling the working rate of the rolling process, it is also possible to control the relative <111> The area ratio of the tungsten phase in the crystal orientation with the orientation difference being -15 to 15 degrees. By combining forging and rolling, a dense tungsten portion 2 having a relative density of 99.5% or more can be formed.
[0117] In addition, a step of forming the high melting point metal portion 3 is performed. The high melting point metal portion 3 has a larger average crystal grain size than the tungsten portion 2. The method of forming the high melting point metal portion 3 includes, for example, a method of preparing a high melting point metal sintered body having a large average crystal grain size in advance and a method of using 3D printing. In particular, 3D printing is preferably used.
[0118] 3D printing is a technique for directly molding a three-dimensional object using a three-dimensional model. Examples of 3D printing include methods using a laser beam or an electron beam.
[0119] 3D printing using a laser beam is called selective laser sintering (SLS). One type of laser sintering is direct metal laser sintering (DMLS). SLS is a method of spreading powder material on a modeling platform and irradiating it with a laser beam. It is a method in which the powder material is melted by irradiation with a laser beam, and then cooled to gradually shape it. After shaping, new powder material is supplied and laser irradiation is repeated.
[0120] DMLS is a laser sintering method that uses high laser output power. DMLS uses an ytterbium laser. SLS uses a carbon dioxide laser.
[0121] SLS and DMLS are methods of sintering powder materials using a laser beam. Another method using a laser beam is selective laser melting (SLM). SLM is a method of gradually shaping powder materials by melting them through laser irradiation. In addition, there is a cladding shaping method called laser metal deposition (LMD) in which powder is blown onto the area irradiated with a laser beam and melted to create a shape.
[0122] 3D printing using an electron beam refers to electron beam melting (EBM). An electron beam is a beam of electrons emitted by irradiating a filament that is heated in a vacuum. Electron beams are characterized by high output power and high speed compared to laser beams. EBM is a technology that melts powdered materials to form shapes. For EBM, there is also a method of using metal wires for forming shapes. When the above-mentioned high-melting-point metals are formed by 3D printing, SLM or EBM is preferred. SLM or EBM is a method of melting metal particles. When the metal particles are melted, it becomes easy to obtain a high-density molded object.
[0123] The process of laying metal powder and solidifying it by irradiating the laser beam using 3D printing with a laser beam is repeated. The process of laying metal powder and solidifying it by irradiating the laser beam is repeated. By using high-melting-point metal powder in the metal powder, the high-melting-point metal part 3 can be molded. In the case of the front-end integrated structure, a method of gradually molding on the lower surface (the opposite side of the high-melting-point metal part 3) can be listed. In the case of the peripheral integrated type, a method of gradually molding around the tungsten part 2 by LMD can be listed.
[0124] In the case of 3D printing, it is preferable to use high melting point metal powder having an average crystal grain size larger than the average crystal grain size of the tungsten portion 2. This makes it easy to manufacture a cathode component that satisfies the formula: B>A and further the formula: B≥1.5A.
[0125] For DMLS and SLS, the laser output power is preferably 100 W or more. For SLM and LMD, the laser output power is preferably 100 W or more. For EBM, the electron beam output power is preferably 2000 W or more.
[0126] The molding speed of SLS, SLM, EBM or LMD is preferably 100 mm / s or more. The molding speed is the speed of scanning the laser or electron beam. If the molding speed is lower than 100 mm / s, the molding speed is slow and mass productivity is reduced. The upper limit of the molding speed is not particularly limited, but it is preferably 5000 mm / s or less. In the case of high melting point metals, if it is faster than 5000 mm / s, the sintering state or the molten state will be uneven, and the density may be reduced more than necessary. If the density is reduced, the strength of the high melting point metal part 3 is reduced.
[0127] By controlling the output power and molding speed of the laser beam or electron beam, the average crystal grain size of the high-melting-point metal part 3 can be increased. By irradiating the tungsten part 2 with a laser beam or an electron beam, it becomes possible to form a concave and convex portion at the bonding interface 5. If the high-melting-point metal part 3 is regarded as a reference, the portion irradiated by the laser beam becomes a concave portion. By setting it within the above-mentioned output power and molding speed range, the value of the concave and convex portion can be set to more than 0.1 mm. By controlling the irradiation diameter of the laser beam or electron beam, the width and spacing of the concave and convex portion can be controlled.
[0128] By forming the high melting point metal part 3 by 3D printing, the shaping method and shaping direction can be determined. <111> The area ratio of the metal phases in the crystal orientation having an orientation difference of -15 to 15 degrees.
[0129] Through 3D printing, Figure 5 As shown in , the hole 7 for joining the support rod 8 is directly molded. If it is a direct molding method, it is also easy to form a thread groove in the hole 7. After the high-melting-point metal part 3 is molded, the hole 7 can also be processed. The tungsten part 2 is formed by forging and rolling, so it is a dense and difficult-to-process material. On the other hand, the high-melting-point metal part 3 is formed by 3D printing, so the high-melting-point metal powder is melted and molded. Therefore, compared with the tungsten part 2, the processability is high and the hole 7 is easy to form. In addition, by not performing rolling processing on the high-melting-point metal part 3, it is possible to control the relative <111> The area ratio of the metal phases in the crystal orientation having an orientation difference of -15 to 15 degrees.
[0130] By using 3D printing, such as Figure 6 As shown in , the high melting point metal portion 3 and the support rod 8 can be integrated. This can reduce the manufacturing cost.
[0131] Through 3D printing, such as Figure 3 As shown in , the fin structure 6 can be formed directly on the high melting point metal portion 3. The high melting point metal portion 3 formed by 3D printing can also be processed to form the fin structure 6. Examples of the processing include cutting processing, laser beam processing, and the like.
[0132] The tungsten portion 2 may be formed by processing the tip of the high melting point metal portion 3 to be sharp. After the tungsten portion 2 is produced, the tip may be sharpened.
[0133] Example
[0134] (Examples 1 to 6, Comparative Example 1)
[0135] The tungsten part 2 is formed. Tungsten powder with an average particle size of 3 μm and an emitter material with an average particle size of 2 μm are mixed in a cylindrical mixing container while rotating the container in the circumferential direction. After that, pre-sintering and electric sintering are performed. Through this process, a cylindrical sintered body (ingot) is manufactured. The manufacturing conditions are shown in Table 1.
[0136] Table 1
[0137]
[0138] Next, the cylindrical sintered body was processed. The processing conditions are shown in Table 2. In addition, all examples were processed by cold working.
[0139] Table 2
[0140]
[0141] After the cylindrical sintered body is processed, the front end is sharpened to produce the tungsten part 2. The obtained tungsten part 2 is cut along the center of the longitudinal direction, and the average crystal grain size of the tungsten phase is measured. In addition, the relative <111> The area ratio of the tungsten phase in the crystal orientation with the orientation difference being -15 to 15 degrees.
[0142] Table 3
[0143]
[0144] Next, the high melting point metal portion 3 is formed on the surface of the tungsten portion 2 using 3D printing. Regarding 3D printing, an example of the front end integrated structure is formed by the SLM method, and an example of the peripheral integrated structure is formed by the LMD method.
[0145] The SLM method and the LMD method set the laser output power to be above 100W. The molding speed is set to 100mm / s to 5000mm / s. The embodiment uses a high-melting-point metal powder having an average crystal grain size larger than the average crystal grain size of the tungsten phase of the tungsten portion 2. The comparative example uses a high-melting-point metal powder having an average crystal grain size smaller than the average crystal grain size of the tungsten phase of the tungsten portion 2. For the cathode component 1 of the embodiment and the comparative example, a fin structure 6 is formed at the high-melting-point metal portion 3. The fin structure has concave fins with a height of 0.5mm and a minimum width of 1mm in a manner surrounding the outer circumference of the high-melting-point metal portion 3. A plurality of fins are formed at a pitch of 2mm.
[0146] In Examples 1 to 5 and Comparative Example 1, a hole 7 for mounting an electrode support rod is formed. In Example 6, the high melting point metal portion 3 and the support rod 8 are integrally molded by 3D printing. In Comparative Example 1, the tungsten portion 2 is manufactured by forging and rolling without using 3D printing, and the cathode component 1 is formed by forming the high melting point metal portion 3 from a part of the tungsten portion 2. That is, the cathode component of Comparative Example 1 is formed of the tungsten portion 2 and the high melting point metal portion 3 by a tungsten alloy containing thorium oxide.
[0147] For the cathode components 1 of the examples and comparative examples, the average crystal grain size and the relative <111> The area ratio of the phase of the above metal with a crystal orientation having an orientation difference of -15 degrees to 15 degrees. In addition, the three-point bending strength of the high-melting-point metal portion 3 was measured. The measurement was performed in accordance with JISR1631. Thus, the cathode components for discharge lamps shown in Tables 4 and 5 were prepared. It should be noted that the three-point bending strength, average particle size, and relative <111> The area ratio of the metal phase having a crystal orientation with an orientation difference of −15 to 15 degrees is measured at a position corresponding to the high melting point metal portion 3 .
[0148] Table 4
[0149]
[0150] Table 5
[0151]
[0152] The bonding interface between the tungsten portion 2 and the high melting point metal portion 3 was observed, and as a result, irregularities of 0.01 mm or more were observed. The oxygen concentration of the high melting point metal portion 3 was measured by infrared absorption method, and as a result, it was 0.1 mass % or less.
[0153] Next, a discharge lamp was produced using the obtained cathode member 1. The distance between the electrodes of the cathode member 1 and the anode member 9 was uniformly set to 5 mm in the discharge lamp. The temperature of the cathode member 1 and the illuminance maintenance factor were measured for each discharge lamp.
[0154] Regarding the temperature of the cathode member 1 , the input power was set to 3000 W, and the temperature of the tungsten portion 2 of the cathode member 1 was measured using an infrared thermal imager when the cathode member 1 was continuously lit for 3 hours.
[0155] The illuminance maintenance rate is measured by a lighting test. The lamp voltage is set to 40V when the light is on, and the lamp voltage is set to 20V when the light is off. Repeat the lighting and off-lighting, and measure the rate of change of illuminance after a total of 10 hours and a total of 700 hours. It is calculated by illuminance maintenance rate (%) = [(illuminance after 10 hours - illuminance after 700 hours) / illuminance after 10 hours] × 100. The illuminance is measured with an illuminometer. The results are shown in Table 6.
[0156] Table 6
[0157]
[0158] As can be seen from the table, the cathode component 1 of the embodiment has an excellent illumination maintenance rate (%). As in Comparative Example 1, it shows the same performance as the cathode component 1 in which the tungsten part 2 and the high melting point metal part 3 are formed of one material. This is because: the heat dissipation is improved by controlling the average crystal grain size and the existence of the fin structure, and the temperature rise of the cathode component 1 is suppressed. In addition, it is also known that even if the emitter material is not contained in the high melting point metal part 3, it has excellent characteristics. Therefore, the amount of emitter material used can also be suppressed.
[0159] Several embodiments of the present invention are illustrated above, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, changes, etc. can be made without departing from the scope of the main purpose of the invention. These embodiments and their modifications are included in the scope and main purpose of the invention, and are also included in the invention described in the claims and their equivalents. The above-mentioned embodiments can be implemented in combination with each other.
Claims
1. A cathode component for a discharge lamp, comprising: Part 1 containing tungsten and emitter material; and a second portion containing a metal different from the emitter material, The first part is bonded to the second part, and a bonding interface between the first part and the second part has a concave-convex shape, and a value of the concave-convex shape is 0.01 mm to 1 mm. When the average crystal grain size of the tungsten phase in the first portion is A μm and the average crystal grain size of the metal phase in the second portion is B μm, A and B are numbers satisfying the formula: B>A and the formula: B≥1.5A, The average crystal grain size of the tungsten phase is 5 μm to 15 μm, The average crystal grain size of the metal phase is 18 μm to 40 μm.
2. The cathode component according to claim 1, wherein When performing electron beam backscatter diffraction analysis of a region within 1 mm from the center of the first portion and having a unit area of 90 μm×90 μm in a cross section passing through the center of the first portion and along the length direction of the first portion, in an Inverse Pole Figure image in a direction perpendicular to the cross section, there is a <111> The area ratio of the tungsten phase in a crystal orientation having an orientation difference of -15 to 15 degrees is 15% to 50%.
3. The cathode component according to claim 2, wherein: When performing electron beam backscatter diffraction analysis of a region within 1 mm from the center of the second portion and having a unit area of 90 μm×90 μm in a cross section passing through the center of the second portion and along the length direction of the second portion, in an Inverse Pole Figure image in a direction perpendicular to the cross section, there is a <111> The area ratio of the metal phase in a crystal orientation having an orientation difference of -15 to 15 degrees is lower than the area ratio of the tungsten phase.
4. The cathode component according to claim 1, wherein The metal includes at least one metal element selected from the group consisting of tungsten and molybdenum.
5. The cathode component according to claim 1, wherein The emitter material includes at least one element selected from the group consisting of thorium and hafnium.
6. The cathode component according to claim 1, wherein The second portion has fins.
7. The cathode component according to claim 1, wherein The second portion has a hole for engaging the support rod.
8. The cathode component according to claim 1, wherein The second portion has a supporting rod. 9 . A discharge lamp comprising the cathode member according to claim 1 .
Citation Information
Patent Citations
Manufacture of alkanol
JP1983000922A
Electrode for discharge lamp and method for manufacturing the same
JP2018077945A
Electrode for discharge lamp, high voltage discharge lamp, lamp unit, and projector-type image display device
CN102379023A
Short-arc discharge lamp
CN103493174A
Short-arc type high-pressure discharge electrode, short-arc type high-pressure discharge tube, short-arc type high-pressure discharge light source device and their manufacturing methods
JP2007095665A